FACTORS AFFECTING PRODUCTIVITY AND THEIR EFFECT ON PROFITS OF TILAPIA (Oreochromis niloticus) FARMERS - Sujono Sujono; Azam Bachur Zaidy; Wahid Nur Fauzi; Sopiyan Danapraja; Nayu Nurmalia (Universitas Mataram, 2025)
The success of tilapia farming is strongly influenced by the productivity it produces, but it often happens that the productivity of tilapia produced by farmers is very low. The purpose of the study was to analyze the factors that affect the productivity of tilapia and its effect on the farmers' profit. The parameters measured include stocking density (X1), feed protein content (X2), pond area (X3), length of maintenance (X4), productivity (Y), and profit (Z). There were 40 respondents from Selomerto Sub-district, Wonosobo Regency, Central Java Province. Data analysis was conducted using SPSS version 22 and pathway analysis. The results of the study indicate that X1, X3, and X4 have a significant effect on Y, while X2 has no effect on Y. Furthermore, X3 and Y have a significant effect on Z, while X1, X2, and X4 have no effect on Z. X1, through Y, has an effect on Z, while X2, X3, and X4, through Y, have no effect on Z. The research data is expected to provide meaningful information to various parties in improving the success of tilapia farming activities carried out by farmers.